Good correlation of the maximal relative bone tracer uptake in SPECT/CT and intraoperative findings of chondral lesions graded with the ICRS. Issue 6 (28th June 2019) - Schiapparelli, Filippo-Franco; Ammann, Nora; Rasch, Helmut; Amsler, Felix; Hirschmann, Michael
Aims and Objectives: It is a pertinent question if SPECT/CT is able to reflect the cartilage status of the knee. Hence, it was the purpose of this study to evaluate the correlation between maximal relative bone tracer uptake (mrBTU) of preoperative SPECT/CT and intraoperative findings of chondral lesions assessed with the International Cartilage Repair Society (ICRS) scoring. Materials and Methods: Thirty-three consecutive patients (male: female=11: 22; mean age ± standard deviation 61±15) with bi- or tri-compartmental osteoarthritis of the knee who underwent SPECT/CT before total knee arthroplasty (TKA) were included. The knee was divided into 11 anatomical regions. In each region, mrBTU values were calculated twice by two observers within a six weeks interval. The intraclass correlation coefficient (ICC) was calculated and mean values were used. Intraoperatively, for every region the cartilage status with regards to ICRS score was assessed. A non-parametrical Spearman's correlation was performed. A factor analysis was performed on mrBTU and ICRS scores (p<0.05). Results: The ICC presented excellent correlations. The Spearman's correlation performed separately on mrBTU and ICRS scores showed diffuse significant correlations which were especially strong between regions of the same knee compartment (p < 0.01). The Spearmann correlation calculated between rmBTU and IRCS scores evidenced very strong correlations on the medial femoral condyle, on the ventral two third of the medial tibia plateau (p < 0.01) and good correlations on the proximal femoral trochlea and on the medial patellar facet (p < 0.05). Conclusion: A highly significant correlation between SPECT/CT and intraoperative findings was demonstrated. The use of an objective measure as the rmBTU for osteoarthritis could overcome the limit of the subjectivity of MRI findings.